A Guidance for Concomitant Drug Reconciliation Prior to Allogeneic Hematopoietic Cell Transplantation in Children and Young Adults - Apsel Winger, Beth; Long, Susie E.; Brooks, Jordan; Gupta, Ashish O.; Dvorak, Christopher C.; Long-Boyle, Janel Renee (Frontiers in Pediatrics, 2021)
Pediatric diseases treated by allogeneic hematopoietic stem cell transplantation (alloHCT) are complex and associated with significant comorbidities and medication requirements that can complicate the transplant process. It is critical to reconcile pre-transplant concomitant medications (pcon-meds) in the weeks prior to alloHCT and to consider the potential for pcon-meds to cause harmful drug-drug interactions (DDIs) or overlapping toxicities with conditioning agents. In this perspective, we describe a systematic process to review pcon-meds and determine the drug modifications needed to avoid DDIs with conditioning regimens. We provide an extensive table (Appendix 1) with a timeline for discontinuation or modification of common pcon-meds that patients are taking when presenting to the HCT medical team. The timeline is based on the pharmacokinetic (PK) properties of both the pcon-meds and the planned conditioning medications, as well as anticipated DDIs. It also accounts for the ages seen at pediatric transplant centers (0-30 years old). Common scenarios, such as when pcon-med discontinuation is not an option, are discussed. Since alloHCT patients are often dependent upon psychiatric medications with problematic DDIs, a table of alternative, non-interacting psychiatric medications is also presented. The appendices provide details regarding how to adjust pcon-meds prior to the start of chemotherapy for children and young adults undergoing alloHCT, however patient-specific circumstances always need to be taken into account. Careful attentiveness to pcon-meds at the time the decision is made to pursue transplant will result in more consistent HCT outcomes, with lower toxicity and increased efficacy of conditioning agents.